Carcinoma and Sarcoma Microenvironment at a Glance: Where We Are - Saggioro, Mattia; D'Angelo, Edoardo; Bisogno, Gianni; Agostini, Marco; Pozzobon, Michela (Frontiers in Oncology, 2020)
Cells and extracellular matrix (ECM) components represent the multifaceted and dynamic environment that distinguishes each organ. Cancer is characterized by the dysregulation of the composition and structure of the tissues, giving rise to the tumor milieu. In this review we focus on the microenvironmental analysis of colon rectal cancer (CRC) and rhabdomyosarcoma (RMS), two different solid tumors. While a lot is known about CRC environment, for RMS this aspect is mostly unexplored. Following the example of the more complete CRC microenvironmental characterization, we collected and organized data on RMS for a better awareness of how tissue remodelling affects disease progression.